2020
DOI: 10.3390/app11010083
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Validation of the GC/FID Method for the Quantification of Fatty Acids in Bee Products

Abstract: To the best of our knowledge, so far, no study has been conducted about the comparison of the total fatty acid concentration in the four bee products (honey, bee pollen, bee bread, and propolis) collected from Lithuania. Therefore, we aimed to optimize the derivatization parameters and to investigate a simple and sensitive gas chromatography-flame ionization detection (GC-FID) method to determine fatty acids. The optimal derivatization parameters were used to analyze fatty acids in the bee products. Regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Regarding the PFB derivatization, it should proceed completely which is consistent with maximizing the peak intensity of the analytes while the intensity of background contamination should be minimized. Contamination is a well-known problem in FA analysis, mainly FA 16:0 and FA 18:0, but in smaller quantities, also short-and medium-chain FAs are known to be contaminants, resulting in an increase of LOD values for FAs with high background contaminations [24,32,44]. Because of this, all chemicals and equipment used should be carefully monitored.…”
Section: Optimization Of Derivatizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the PFB derivatization, it should proceed completely which is consistent with maximizing the peak intensity of the analytes while the intensity of background contamination should be minimized. Contamination is a well-known problem in FA analysis, mainly FA 16:0 and FA 18:0, but in smaller quantities, also short-and medium-chain FAs are known to be contaminants, resulting in an increase of LOD values for FAs with high background contaminations [24,32,44]. Because of this, all chemicals and equipment used should be carefully monitored.…”
Section: Optimization Of Derivatizationmentioning
confidence: 99%
“…FAMEs as well as other derivatized FAs are usually detected by flame ionization detector (FID) or a mass spectrometer (MS). While FIDs are still important for the analysis of FAs, especially when analyzing the total fatty acid (TFA) profile [23][24][25], they do not provide mass spectral information, which results in a lack of specificity. Moreover, quantification is further complicated by the requirement for baseline separation of individual FAs.…”
Section: Introductionmentioning
confidence: 99%
“…The quantity of lipids compounds present in honey is small (0.04%), comprising glycerides, sterols, and phospholipids, followed by various fatty acids including palmitic, oleic, lauric, miristic, stearic and linoleic [53]. As the lipid content of honey is essentially composed from free fatty acids, their importance for health is significant, as they play an important role in the composition of cells membranes, dictating the growth and development of the human body [62]. Even if some studies have revealed the presence of these fatty acids in pollen [63,64] there is still limited research regarding their presence in honey.…”
Section: Lipidsmentioning
confidence: 99%
“…Even if some studies have revealed the presence of these fatty acids in pollen [63,64] there is still limited research regarding their presence in honey. However, Jarukas et al (2021) [62], have compared the presence of fatty acids in some bee products (bee bread, bee pollen, propolis and honey), with the results showing that the quantity of fatty acids present in honey was lower than in the other three bee products.…”
Section: Lipidsmentioning
confidence: 99%
“…Fatty acids in the form of methyl esters were also determined using the GC-FID technique in four bee products. The authors of the study compared the total fatty acid concentration (saturated, unsaturated, omega-3, omega-6, the ratio of saturated and unsaturated, omega-3/omega-6 fatty acids and trans fatty acids) [78]. Fruehwirth et al [79] investigated the lipid oxidation in stored margarine using GC-FID method.…”
Section: Gas Chromatography Gc In Analysis Of Selected Bioactive Compounds In Food Samplesmentioning
confidence: 99%